Effect of glucocorticoid administration on the steroid profile. Issue 6 (6th February 2018) - Coll, Sergi; Matabosch, Xavier; Garrostas, Lorena; Perez‐Maña, Clara; Ventura, Rosa
Abstract: The steroid profile (SP) is a powerful tool to detect the misuse of endogenous anabolic androgenic steroids in sports, and it is included in the Athlete Biological Passport (ABP). Glucocorticoids (GCs), which are widely prescribed in sports and only prohibited in competition by systemic routes, inhibit the hypothalamic‐pituitary‐adrenal axis. Since the metabolites monitored in the SP have a partial adrenal origin, their excretion in urine might be altered by GCs consumption. The aim of the present work was to investigate if GCs administered by either systemic or local routes could influence the SP parameters. Three of the most frequently detected GCs in sports (prednisolone, betamethasone, and triamcinolone acetonide) were administered to healthy male and female volunteers (n=40) using different administration routes (topical, oral, and intramuscular administration at different doses). In total, 66 administrations of GCs were performed. Urine samples were collected before and after GCs administration. The SP was measured using gas chromatography‐mass spectrometry. The excretion rates of the SP metabolites decreased after systemic GCs administration. This excretion decrease showed to be associated with the dose and the administration route. However, the individual evaluation of the SP ratios (T/E, A/T, A/Etio, 5αAdiol/5βAdiol, and 5αAdiol/E) led to normal sequences for all the conditions tested. Therefore, GCs administration did not produce misinterpretations on the ABP evaluation. According to these results, GCs administration should not distort the establishment of normal ranges of the SP ratios, and does not need to be considered a confounding factor in the SP evaluation. Abstract : The excretion rates of steroid profile metabolites are significantly altered after the systemic glucocorticoid administration. However, the ratios of the steroid profile are not modified after glucocorticoid consumption. Therefore, glucocorticoids cannot be considered a confounding factor of the steroid profile.